Search for Pair Production of a Heavy Up-Type Quark Decaying to a W Boson and a b Quark in the lepton plus jets Channel with the ATLAS Detector - Onofre, A. (2012)
A search is presented for production of a heavy up-type quark (t′) together with its antiparticle, assuming subsequent decay to a W boson and a b quark, t′¯t′→W+bW−¯b. The search is based on 1.04  fb−1 of proton-proton collisions at √s=7  TeV collected by the ATLAS detector at the CERN Large Hadron Collider. Data are analyzed in the lepton+jets final state, characterized by a high transverse momentum isolated electron or muon, high missing transverse momentum, and at least three jets. No significant excess of events above the background expectation is observed. A 95% C.L. lower limit of 404 GeV is set for the mass of the t′ quark.